Enhanced photoemission from laser-excited plasmonic nano-objects in periodic arrays. (14th June 2016) - Fedorov, N; Geoffroy, G; Duchateau, G; Štolcová, L; Proška, J; Novotný, F; Domonkos, M; Jouin, H; Martin, P; Raynaud, M
Abstract: The process of photoelectron emission from gold surfaces covered with nano-objects that are organized in the form of a periodic array is addressed in the short laser pulse regime ( ⩽ 50 fs) at moderate intensities ∼ 10 10 W cm −2 and for various laser wavelengths. The emission spectrum from a gold single crystal measured under the same conditions is used for reference. The comparison of the photo-emission yield and the energy of the ejected electrons with their counterparts from the (more simple) reference system shows that the periodic conditions imposed on the target surface drastically enhance both quantities. In addition to the standard mechanism of Coulomb explosion, a second mechanism comes into play, driven by surface plasmon excitation. This can be clearly demonstrated by varying the laser wavelength. This interpretation of the experimental data is supported by predictions from model calculations that account both for the primary quantum electron emission and for the subsequent surface-plasmon-driven acceleration in the vacuum. Despite the fact that the incident laser intensity is as low as ∼ 5 × 10 10 W cm −2, such a structured target permits generating electrons with energies as high as 300 eV. Experiments with two incident laser beams of different wavelengths with an adjustable delay, have also been carried out. The results show that there exist various channels for the decay of the photo-emission signal, depending on the target type. These observations are shedding light on the various relaxation mechanisms that take place on different timescales.